Pengaruh Stres Kerja Terhadap Kinerja Aparatur Sipil Negara Pada Kantor Sekretariat Daerah Kabupaten Batang Hari - Ade Jermawinsyah Zebua; Azwar Anas (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2022)
Competition and increasingly high demands for professionalism create a lot of pressures that must be faced by individuals in the work environment. Employees who are always busy with task completion deadlines, the demands of roles in the workplace are increasingly diverse and sometimes conflict with one another, family problems, excessive workloads, and many other challenges that make stress a factor that is almost impossible to overcome. avoided. Organizational performance is determined by employee performance as an individual human being where work behavior becomes the main resource in achieving the desired organizational goals. Employee performance is a real behavior that is produced by everyone as work performance produced by employees in accordance with their role in an organization. This study aims to determine the effect of Performance Stress on the Performance of State Civil Apparatus at the Regional Secretariat Office of Batang Hari Regency. The research method used is quantitative research. The sample in this study were 34 civil servants. The sampling technique used is random sampling. Data were obtained from respondents by using a data collection tool in the form of a questionnaire. The data analysis used is simple linear regression analysis, statistical description of variables, validity and reliability testing and t-statistical test.